A method for preparing a high-temperature-resistant phosphoric acid-based surface coating

CN122978751APending Publication Date: 2026-10-27广西漫真新材料有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611138350.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-29
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

但现有磷酸盐涂层仍存在多处性能短板:其一,基体化学性能活泼,在调配过程极易先与某一组分发生化学反应生成惰性相,不易在常温下制备;其二,磷酸盐体系功能性不足,较硅酸盐体系相比难以通过添加其他化学物质增加额外性能;其三,涂层热膨胀系数与金属基材匹配度不足,在反复冷热循环过程中,体积胀缩产生的内应力易引发涂层膨胀开裂、片状剥落,抗热震性能难以满足交变高温工况;其四,纯磷酸盐固化基体的致密度与刚性有限,涂层表面硬度与耐磨性能存在明显缺陷,在存在摩擦、冲刷的高温工况下使用寿命较短

Benefits of technology

[0034]针对背景技术所述的四种性能短板,本涂料通过调配草酸溶液的质量分数以达到控制金属离子可溶性螯合物数量的效果,进而调控配方间物质的化学反应速率,从而解决了组分间化学反应发生先后的问题;本涂料通过构建致密的涂料骨架实现了在骨架中嵌入其他性能改良物质;本涂料在配方中加入氧化硼和石英,通过石英高低温物态变化与氧化硼改变应力分布的作用缓解了因热胀冷缩产生的裂纹和性能失效;本涂料通过在制备过程中加入大量金属氧化物等物质明显提升了涂料整体的硬度与刚度,提升了材料性能。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a high-temperature-resistant phosphoric acid-based surface coating preparation method. Alumina, chromium oxide green and silicon carbide are used as a skeleton, and a skeleton promoter, a solidification regulator and other raw materials are added in the preparation process, so that the high-temperature-resistant, anti-expansion-cracking and surface stress-reducing effects are achieved. By adjusting the concentration and mass proportion of the solidification regulator, the balanced reaction speed is achieved, the phosphorus ions are slowly released, the coating is more dense, and a continuous inorganic skeleton network is formed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of fine chemical coating materials and application technology, specifically relating to a method for preparing a phosphate-based high-temperature resistant surface coating. Background Technology

[0002] Surface coating technology refers to surface engineering techniques that construct functional films on the surface of a substrate to achieve multiple benefits, such as improved surface smoothness, enhanced mechanical hardness, and barrier against corrosive media. It has wide applications in machinery manufacturing, metallurgy, chemical engineering, energy and power, and consumer hardware. Most industrial components and consumer products require surface coating to improve performance and extend service life. However, conventional coatings commonly suffer from performance failure under high-temperature operating conditions. Possible reasons include: organic coatings rely on polymer resins as the film-forming phase, but at high temperatures, these resins are prone to carbon chain breakage, matrix oxidation and decomposition, and coating volatilization, carbonization, and powdering, resulting in a loss of resin performance; while ordinary inorganic coatings have better thermal stability than organic systems, they are still prone to crystal transformation, volume distortion, and binder phase failure under sustained high temperatures and alternating hot and cold environments, making it difficult to maintain structural and functional integrity over the long term. Therefore, ensuring coating performance stability under high-temperature conditions is extremely difficult.

[0003] In the current field of high-temperature protective coatings, alkali metal silicate system coatings are the most widely used. From the perspective of film formation principle, this system uses alkali metal silicates such as sodium silicate and potassium silicate as the film-forming matrix. It forms a Si-O-Si three-dimensional inorganic network through room-temperature dehydration condensation and solidifies into a film. Performance is further optimized through silica sol and borate modification. From the perspective of cost and construction characteristics, silicate raw materials are industrially mature and inexpensive to purchase. The single-component system is stable in storage and has a low construction threshold, allowing for various processes such as brushing, spraying, and rolling. It has good compatibility with porous inorganic substrates such as cement, brick, and insulation cotton, and is widely used in applications such as the exterior walls of civilian stoves, fireproofing of building steel structures, protection of ordinary thermal pipelines, and exterior cladding of kiln insulation layers. However, the heat resistance of this system has a significant upper limit: the long-term service temperature of ordinary sodium-based silicate coatings is only 600~800℃, and the short-term peak temperature resistance of high-modulus potassium silicate and lithium silicate modified formulations is only close to 1000℃. The fundamental reason is that alkali metal components are prone to volatilization at high temperatures, and the silicon-oxygen network undergoes glass transition and softening, resulting in a sharp drop in coating strength, powdering and peeling, which cannot meet the requirements of long-term high-temperature protection above 800℃.

[0004] Phosphate-based coatings are another mainstream inorganic high-temperature coating, generally exhibiting superior temperature resistance compared to silicate systems. Their main components are fillers (typically corundum powder), binders (typically metal phosphate compounds), and other ingredients. This system uses acidic phosphates such as aluminum dihydrogen phosphate as the core binder phase, which cures into a film through acid-base crosslinking reactions with metal oxides. At high temperatures, it gradually transforms into ceramic phases such as metaphosphate and orthophosphate, achieving long-term service temperatures of 1000–1500°C. It is widely used in high-temperature corrosion protection applications on metal substrates, such as engine exhaust pipes, boiler tube walls, and heat treatment fixtures. However, existing phosphate coatings still have several performance shortcomings: First, the substrate is chemically reactive and easily reacts with a certain component during the formulation process to form an inert phase, making it difficult to prepare at room temperature; second, the phosphate system lacks functionality and is difficult to enhance by adding other chemical substances compared to silicate systems; third, the coating's coefficient of thermal expansion is not well matched with the metal substrate, and the internal stress generated by volume expansion and contraction during repeated heating and cooling cycles can easily cause the coating to expand, crack, and peel off in flakes, making it difficult to meet the thermal shock resistance requirements of alternating high-temperature conditions; fourth, the density and rigidity of the pure phosphate-cured substrate are limited, resulting in significant defects in the surface hardness and wear resistance of the coating, leading to a short service life under high-temperature conditions involving friction and erosion. Summary of the Invention

[0005] To address the aforementioned problems, this invention provides a method for preparing a high-temperature resistant phosphate-based surface coating. This method primarily improves the heat resistance and overall performance of the coating by altering the filler and binder compositions to enhance various material properties.

[0006] Specifically, the filler and adhesive components of the present invention are composed of the following components by mass percentage: Coating filler: 45% Skeletal accelerator: 30% Curing regulator: 15% Quartz powder (SiO2): 5% Boron oxide (B₂O₃): 5% The coating filler is composed of the following substances by mass percentage: Alumina (Al2O3) 60% Chromium oxide green (Cr2O3) 25% Silicon carbide (SiC) 15% The skeleton accelerator is composed of the following substances by mass percentage: Aluminum dihydrogen phosphate (Al(H2PO4)3) 55% Chromium phosphate (CrPO4) 18% Aluminum polyphosphate (Al(PO3)3) 12% Chromium dihydrogen phosphate (Cr(H2PO4)3) 15% The four substances in the skeleton accelerator decompose at different temperatures, allowing for the slow release of phosphate ions during coating formation. At high temperatures, the acid salts are completely dehydrated, and the polyphosphate chains further crosslink. The aluminum polyphosphate and chromium polyphosphate intertwine to form a continuous three-dimensional inorganic polymer network. Chromium phosphate crystals are dispersed within this network as fillers, dispersing stress, reducing shrinkage cracking, and forming a rigid three-dimensional crystalline skeleton with covalent bonds.

[0007] The curing modifier is composed of the following substances by mass percentage: n-Propanol (C3H8O) 35-45% Magnesium oxide (MgO) 20% Zinc oxide (ZnO) 30% Oxalic acid (H2C2O4) 5-15% In the curing regulator, n-propanol is used as a solvent. It has a boiling point of about 97°C and good miscibility with phosphate aqueous solution. It can effectively reduce the overall viscosity of the system and improve its fluidity. During low-temperature drying at 100-150℃, n-propanol gradually and steadily volatilizes, and completely decomposes and escapes during subsequent high-temperature heating, leaving no residue in the three-dimensional framework of the coating and not affecting the formation and densification of the high-temperature crystalline phase structure. Oxalic acid is a strong complexing dibasic organic acid that can form stable soluble chelates with metal ions such as Al³⁺, Mg²⁺, and Zn²⁺ in the system, delaying the acid-base crosslinking reaction between acidic phosphates and metal oxides, significantly extending the curing induction period. As the curing temperature increases, the chelates gradually decompose, and the metal ions are slowly released, ensuring a smooth and sufficient crosslinking reaction, avoiding insufficient reaction or excessive reaction of reactants caused by rapid local gelation. Magnesium oxide is highly basic and can undergo rapid acid-base neutralization with acidic phosphates to generate magnesium phosphate, which participates in the crosslinking construction of the three-dimensional network. Zinc oxide has lower reactivity than magnesium oxide, and its crosslinking reaction with acidic phosphates is slow and prolonged, gradually generating the zinc phosphate phase at the intermediate temperature stage, participating in the later densification of the network.

[0008] Phosphate-based coatings are brittle after curing, and their coefficient of thermal expansion differs significantly from that of metals and refractory substrates. Sudden temperature changes can generate enormous thermal stress at the interface and within the coating, easily leading to cracking, peeling, and complete loss of high-temperature protection. The reversible crystal transformation between α-quartz and β-quartz at 573℃ can buffer thermal stress through volume changes and induce uniform microcracks to deflect and dissipate the propagation energy of the main crack, reducing the thermal expansion mismatch with the substrate. Furthermore, quartz powder itself has strong chemical inertness and excellent thermal stability, ensuring the structural integrity and protective capability of the coating under multiple thermal cycles for an extended period.

[0009] The main reasons for surface coating cracking at high temperatures are dehydration shrinkage due to thermal expansion, thermal stress, and porosity concentration. Using boron oxide in the binder will cause it to melt first during the coating heat treatment process, forming a low-viscosity borate glass liquid phase. This liquid phase fills the gaps between particles and internal pores through capillary action, significantly increasing the coating density and reducing crack formation. Furthermore, the coefficient of thermal expansion of borate glass is much lower than that of pure phosphate matrix. Introducing it in appropriate amounts can lower the overall coefficient of thermal expansion of the coating, reducing the difference in thermal expansion between the coating and the metal / ceramic substrate, and significantly reducing surface tensile stress caused by the mismatch between thermal expansion and contraction during heating and cooling.

[0010] The preparation process of the curing regulator is as follows: 1. Weigh each raw material precisely according to the mass ratio; grind magnesium oxide and zinc oxide at room temperature for 10 minutes to mix thoroughly and obtain a uniformly mixed metal oxide powder, then seal and store for later use.

[0011] 2. Stir 70% n-propanol at low speed of 150 rpm, add all the oxalic acid in 3 batches at room temperature, with each batch being equal in volume and 3 minutes apart, and continue stirring until the oxalic acid is completely dissolved to obtain oxalic acid-n-propanol mother liquor.

[0012] 3. Add the remaining 30% of n-propanol to the beaker, pour in the pretreated oxide powder, and stir for 5 minutes to completely wet the powder with the solvent, forming a coarse suspension without dry powder lumps or sediment.

[0013] 4. The beaker containing the coarse suspension is ultrasonically vibrated at room temperature for 15 minutes to obtain a highly dispersed oxide suspension.

[0014] 5. The oxalic acid-n-propanol mother liquor was heated and stirred at a constant speed of 220 rpm. The water bath heating rate was set to 2℃ / min. After the system temperature reached 45℃, it was kept at that temperature for 5 minutes to ensure that the temperature of the solution was uniform and stable throughout.

[0015] 6. Slowly add the ultrasonicated oxide suspension to the oxalic acid-n-propanol mother liquor at a constant dropping rate of 1.2~1.8 mL / min.

[0016] 7. After the addition is complete, keep the stirring rate constant and gradually increase the temperature of the system to 65℃ by stirring at a rate of 1℃ / min.

[0017] 8. After the system temperature reaches 65℃, maintain the water bath temperature constant and keep it warm for 35 minutes under continuous stirring.

[0018] 9. After the heat preservation is completed, the reaction solution is subjected to a second ultrasonic vibration, with the power set to 250W and the ultrasonic time set to 10min.

[0019] 10. Seal and package the solution.

[0020] The preparation process of the high-temperature resistant phosphate-based surface coating is as follows: 1. Place the five powder raw materials, namely alumina, chromium oxide green, silicon carbide, quartz powder and boron oxide, at 120℃ and dry them for 1 hour, then cool them to room temperature.

[0021] 2. Weigh out the cooled alumina, chromium oxide green, silicon carbide and quartz powder according to the formula ratio, ball mill them until the particle size distribution of the fillers is uniform and they are initially mixed, and record it as powder A.

[0022] 3. Weigh out aluminum dihydrogen phosphate crystals according to the formula, add deionized water, and control the solid-liquid mass ratio at 1:0.8. Stir at 150 r / min at room temperature until dissolved.

[0023] 4. Mix chromium phosphate and chromium dihydrogen phosphate, add 80°C deionized water and stir until completely dissolved.

[0024] 5. Slowly add aluminum polyphosphate powder to 50℃ deionized water and stir at low speed until dissolved.

[0025] 6. Add the mixed solution of chromium phosphate and chromium dihydrogen phosphate dropwise to the aluminum dihydrogen phosphate solution. Maintain a stirring speed of 200 r / min throughout the dropwise addition. After the dropwise addition is complete, slowly pour in the aluminum polyphosphate colloid and curing regulator, and continue stirring to obtain a uniform composite phosphate adhesive base liquid, which is denoted as solution A.

[0026] 7. Heat solution A to 80°C at a rate of 2°C / min, and stir for 30 min to promote the initial polymerization reaction between phosphates.

[0027] 8. Continue to heat solution A to 105℃ at a rate of 1℃ / min, and keep it at this temperature for 1 hour to allow the system to undergo a condensation reaction and remove some of the free water. Keep stirring at a low speed during the heat preservation period.

[0028] 9. Soak boron oxide powder in anhydrous ethanol, then slowly add it to solution A.

[0029] 10. Add powder A to solution A in batches of 40%, 35%, and 25%, and stir to prevent powder from clumping together. The mixture is then labeled as slurry A.

[0030] 11. The mixed slurry A is subjected to ultrasonic vibration. The ultrasonic power is set to 300 W, the frequency to 40 kHz, and the temperature is controlled at 50℃. The ultrasonic treatment lasts for 25 min.

[0031] 12. Transfer the homogenized slurry A into a vacuum dryer and vacuum process it.

[0032] 13. After releasing the vacuum, transfer slurry A to a constant temperature water bath, heat it to 90°C, and keep it warm for 1 hour.

[0033] 14. Pack the slurry into a sealed bag and store at room temperature. Beneficial effects

[0034] To address the four performance shortcomings mentioned in the background technology, this coating controls the amount of soluble chelates of metal ions by adjusting the mass fraction of the oxalic acid solution, thereby regulating the chemical reaction rate between substances in the formulation and solving the problem of the order of chemical reactions between components. This coating also incorporates other performance-enhancing substances within a dense coating framework. Furthermore, the addition of boron oxide and quartz to the formulation mitigates cracking and performance failure caused by thermal expansion and contraction through the high- and low-temperature physical state changes of quartz and the stress distribution alteration effect of boron oxide. Finally, the addition of a large amount of metal oxides and other substances during the preparation process significantly improves the overall hardness and stiffness of the coating, thus enhancing material performance. Detailed Implementation

[0035] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other implementation methods obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Example

[0036] The curing regulator, oxalic acid, was set at 5% by mass, and n-propanol at 45% by mass. The remaining coating formulation and operating steps were as described above. The prepared coating was applied to magnesium oxide ceramic and cured in a 120°C constant temperature drying oven for 2 hours. Example

[0037] The curing regulator, oxalic acid, was set at 15% by mass, and n-propanol at 35% by mass. The remaining coating formulation and operating steps were as described above. The prepared coating was applied to magnesium oxide ceramic and cured in a 120°C constant temperature drying oven for 2 hours.

[0038] Technical effects of the present invention: The adhesion of the coating prepared in the example was tested according to the ASTM D3359 test standard, as well as the adhesion after boiling. After coating, the surface condition of the coating and the coated film were observed, which shows that the present invention has achieved good technical results.

[0039] This disclosure has been described with reference to the foregoing embodiments; however, these embodiments are merely examples for implementing this disclosure. It must be noted that the disclosed embodiments do not limit the scope of this disclosure. On the contrary, any changes and modifications made without departing from the spirit and scope of this disclosure are within the scope of patent protection of this disclosure.

Claims

1. A method for preparing a high-temperature resistant phosphate-based surface coating, characterized in that: The composition, by mass percentage, consists of the following components: Alumina (Al2O3) 27% Chromium oxide green (Cr2O3) 11.25% Silicon carbide (SiC) 6.75% Skeletal accelerator: 30% Curing regulator: 15% Quartz powder (SiO2): 5% Boron oxide (B2O3): 5%.

2. The method for preparing a high-temperature resistant phosphate-based surface coating according to claim 1, characterized in that: The skeleton accelerator consists of the following components by mass percentage: Aluminum dihydrogen phosphate (Al(H2PO4)3) 55% Chromium phosphate (CrPO4) 18% Aluminum polyphosphate (Al(PO3)3) 12% Chromium dihydrogen phosphate (Cr(H2PO4)3) 15%.

3. The method for preparing a high-temperature resistant phosphate-based surface coating according to claim 1, characterized in that: The curing regulator, by mass percentage, consists of the following components: n-Propanol (C3H8O) 35~45% Magnesium oxide (MgO) 20% Zinc oxide (ZnO) 30% Oxalic acid (H2C2O4) 5~15%.

4. The method for preparing a high-temperature resistant phosphate-based surface coating according to claim 1, characterized in that: The preparation method of the high-temperature resistant phosphate-based surface coating is as follows: Five powder raw materials—alumina, chromium oxide green, silicon carbide, quartz powder, and boron oxide—are placed at 120°C, dried for 1 hour, and then cooled. Afterward, they are ball-milled until the filler particle size distribution is uniform and preliminarily mixed. Aluminum dihydrogen phosphate crystals are weighed and added to deionized water at a solid-liquid mass ratio of 1:0.8, stirred at room temperature until dissolved. Then, chromium phosphate, chromium dihydrogen phosphate, and aluminum phosphate are added to deionized water at 80°C and 50°C respectively, stirred until dissolved. Finally, while stirring, the mixed solution of chromium phosphate and chromium dihydrogen phosphate is dropwise added to the phosphate solution. After the aluminum dihydrogen phosphate solution is added dropwise, aluminum polyphosphate and curing regulator are poured in and stirred until they are evenly mixed. Then, the solution is heated to 80°C at a rate of 2°C / min and stirred for 30 minutes. The temperature is then increased to 105°C at a rate of 1°C / min and held at this temperature for 1 hour. Boron oxide impregnated with anhydrous ethanol, and aluminum oxide, chromium oxide green, silicon carbide, quartz powder and boron oxide mixed powder are added in batches of 40%, 35% and 25% respectively. After the addition is completed, the mixture is ultrasonically vibrated at 50°C for 25 minutes. After ultrasonic vibration, vacuum treatment is performed and then the mixture is held at 90°C for 1 hour.

5. The method for preparing a high-temperature resistant phosphate-based surface coating according to claim 1, characterized in that: The preparation method of the curing regulator is as follows: Magnesium oxide and zinc oxide are ground into uniformly mixed metal oxide powders. Propanol is divided into two batches of 70% and 30% by mass. All oxalic acid is added to the 70% propanol in three batches while stirring, with each batch being equal in volume and spaced 3 minutes apart. Stirring is continued until the oxalic acid is completely dissolved. The remaining 30% propanol is then poured into the magnesium oxide and zinc oxide powders and ultrasonically vibrated for 15 minutes. The 30% propanol solution is then stirred while heating at a rate of 2°C / min. After the temperature reaches 45°C, it is held at that temperature for 5 minutes. After holding at that temperature, the 30% propanol solution is added to the 70% propanol solution. The system is heated and stirred at a rate of 1°C / min, and the system temperature is gradually increased to 65°C. The temperature is held for 35 minutes and then ultrasonically vibrated for 10 minutes.